Naïve CD4+ T Cell Lymphopenia and Apoptosis in Chronic Hepatitis C Virus Infection Is Driven by the CD31+ Subset and Is Partially Normalized in Direct-Acting Antiviral Treated Persons - Auma, Ann W.N.; Shive, Carey L.; Lange, Alyssa; Damjanovska, Sofi; Kowal, Corinne; Zebrowski, Elizabeth; Pandiyan, Pushpa; Wilson, Brigid; Kalayjian, Robert C.; Canaday, David H.; Anthony, Donald D. (Frontiers in Immunology, 2021)
Background The mechanisms underlying naïve CD4+ lymphopenia during chronic Hepatitis C Virus (HCV) infection are unclear. Whether direct-acting antiviral (DAA) therapy restores peripheral naïve CD4+ T cell numbers and function is unknown. Methods We enumerated frequencies and counts of peripheral naïve CD4+, CD4+CD31+ and CD4+CD31- T cells by flow cytometry in a cross sectional analysis comparing chronic HCV infected (n=34), DAA-treated(n=29), and age-range matched controls (n=25), as well as in a longitudinal cohort of HCV DAA treated persons (n=16). The cross-sectional cohort was stratified by cirrhosis state. Cell apoptosis/survival (AnnexinV+7AAD+/BCL-2 labeling) and cell cycle entry (Ki67 expression) of CD31+ and CD31- naïve CD4+ T cells was analyzed directly ex vivo and following 3 and 5 days of in vitro culture with media, interleukin (IL) -7 or CD3/CD28 activator. Results In the cross-sectional cohort, naïve CD4+ proportions were lower in chronic HCV infected persons compared to controls and DAA-treated persons, an effect in part attributed to cirrhosis. Age was associated with naïve cell counts and proportions in HCV infected and treated persons as well. Naïve CD4+ cell proportions negatively correlated with plasma levels of soluble CD14 following therapy in DAA-treated persons. Naïve CD4+ cells from HCV infected persons exhibited greater direct ex vivo apoptosis and cell-cycling compared to cells from DAA-treated persons and controls, and this was localized to the CD4+CD31+ subset. On the other hand, no remarkable differences in expression of BCL-2 or IL-7 Receptor (CD127) at baseline or following in vitro media or IL7 containing culture were observed. In the longitudinal cohort, naïve CD4+CD31+/CD31- ratio tended to increase 24 weeks after DAA therapy initiation. Conclusions Activation and apoptosis of peripheral naïve CD4+CD31+ T cells appear to contribute to naïve CD4+ lymphopenia in chronic HCV infection, and this defect is partially reversible with HCV DAA therapy. Age and cirrhosis -associated naïve CD4+ lymphopenia is present both before and after HCV DAA therapy. These findings have implications for restoration of host immune function after DAA therapy.